Computer Algorithm‐Based Hydroxyurea Dosing Facilitates Titration to Maximum Tolerated Dose in Sickle Cell Anemia. (16th July 2020) - Oldham, Mahogany; Conrey, Anna; Pittman, Corinne; Fisher, Cameron; Hargrett, Simone; West, Kamille; Jackson, Mary; Martin, Staci; Hsieh, Matthew M.; Jeffries, Neal; Kaplarevic, Mihailo; Johnson, Dachelle; et al.
Abstract: Adults with sickle cell disease (SCD) experience acute and chronic complications and die prematurely. When taken at maximum tolerated dose (MTD), hydroxyurea prolongs survival; however, it has not consistently reversed organ dysfunction. Patients also frequently do not take hydroxyurea, at least in part because of physician discomfort with prescribing hydroxyurea. We sought to develop a computer program that could easily titrate hydroxyurea to MTD. This was a single‐arm, open‐label pilot study. Fifteen patients with homozygous SCD were enrolled in the protocol, and 10 patients were followed at baseline and then for 1 year after hydroxyurea initiation or dose titration. Fetal hemoglobin significantly increased in all 10 patients from 8.3% to 25.1% ( P < .001). Nine patients were titrated to MTD in an average of 7.9 months, and the tenth patient's hydroxyurea dose was increased to 33 mg/kg/day. Computer program dosing recommendations were the same as manual dosing decisions made using the same algorithm for all patients and at all times. We also evaluated markers of cardiopulmonary, liver and renal damage. Although cardiopulmonary function did not significantly improve, direct bilirubin and alanine aminotransferase levels significantly decreased ( P < .001 and P < .01, respectively). Last, although kidney function did not improve, degree of proteinuria was significantly reduced ( P < .05). We have developed a computer program that reliably titrates hydroxyurea to MTD. A larger study is indicated to test the program either as a computer program or a downloadable application.